Too close to the edge - Dunlap, Susan (New York : St. Martin's Press, 1987)
Jill Smith, a smart, tough Berkeley detective, investigates when a handicapped woman is found murdered at a construction site.
"A Jill Smith mystery.".
Booklist.
Wilson's Fiction.
Adult.
Adult
Keywords: Policewomen -- California -- Berkeley -- Fiction; Smith, Jill (Fictitious character) -- Fiction; Mystery fiction; Detective and mystery stories